Pengaruh Metode Bercerita Terhadap Minat Belajar Siswa Kelas 5 di SDN 7 Sambik Bangkol - , Pariyono; Habiburrahman, Lalu; Muhajirin, M. (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This research is based on the lack of interest in learning of grade 5 students at SDN 7 Sambik Bangkol. This research is a quantitative research with a field research design where the researcher goes directly to the research location, namely class 5 at SDN 7 Sambik Bangkol with a sample of 34 students and uses a pretest and posttest. There are 2 research variables, namely student learning interest as an independent variable (x) and storytelling method as a dependent variable (y). Instrument validation in this study used expert judgment. Analysis of this research data is descriptive analysis and assumption testing as well as using the t test in testing research hypotheses. The results of this research have a significant effect between variable x and variable y as evidenced by the results of the t test carried out, namely the t value < 0.05 in accordance with the decision making requirements, if the t value < 0.05 then there is a significant influence on the 2 variables studied. The result of the t value in this research is 0.003 < 0.05, meaning that the hypothesis in this research is accepted.